AUTOPHAGY AND RENAL CELL CARCINOMA: WHAT DO WE KNOW SO FAR? - Radovanović, Milan (Medicinski podmladak, 2021)
Renal cell carcinoma (RCC) is the most common type of kidney tumor in adults, accounting for approximately 90% of kidney malignances and it occurs usually between ages of 60 and 70 years. The 5-year overall survival rate for all RCC types is 49%. Since RCCs are resistant to many different radio and chemotherapeutics that act via apoptosis induction, the development of new approaches to RCC treatment is still in the focus of modern urology. In particular, in recent years, autophagy in RCC has been widely studied as a mechanism of cell extinction through which tumor cells can overcome resistance to apoptosis activation therapy. Autophagy is often referred to as a double-edged sword because it can be a process that allows cells of cancer to survive and, on the other hand and under other conditions, it can be a cell dying mechanism, independent or closely related to other cell death modalities, like apoptosis and necrosis. The central role in the tempering of the process of autophagy, in general, belongs to the mTOR complex (mammalian target of rapamycin), which integrates numerous signals that affect autophagy, such as growth factors, nutrients, various stressors and the energy status of the cell. In RCC, the most important is PI3K/AKT/mTOR signaling pathway since activation of this signaling leads to survival of tumor cells through mTOR activation and thus autophagy inhibition. Up to now, it was found that autophagy markers such as Beclin-1 and LC3-II can be considered as prognostic markers for RCC since the high level of Beclin 1 was detected in tissues and cells of RCC (A498 and ACHN cell lines) and that tumor cell mobility is promoted by the up-regulated expression of LC3.Therefore, a progress in RCC therapy can be expected from the development and synthesis of specific compounds targeting autophagy as well as the therapy based on their combination.
Keywords: renal cell carcinoma; autophagy; mTOR complex